The Influence of Fintech on The Level of Credit Disbursement for MSMEs - Ralahallo, Fransiska Natalia; mayndarto, Eko Cayo; Mamusung, Robby Tanod (PT. Anagata Sembagi Education, 2025)
This study aims to analyze the impact of financial technology (fintech) utilization on credit disbursement levels to Micro, Small, and Medium Enterprises (MSMEs). The background of this research lies in the limited access of MSMEs to formal financing, which is often constrained by collateral requirements, complex bureaucratic procedures, and a lack of credit information. Fintech emerges as a digital solution offering faster, simpler loan processes without the need for physical collateral. This study adopts a quantitative approach using a survey method, with data collected through questionnaires distributed to 100 MSME actors who utilize fintech services. The results of linear regression analysis indicate that fintech has a significant effect on increasing credit disbursement. In other words, the higher the utilization of fintech, the greater the opportunity for MSMEs to access financing. The study concludes that fintech plays an essential role in promoting financial inclusion; however, this must be supported by improved financial literacy and appropriate regulatory oversight to ensure its long-term benefits.